Antibodies of predetermined specificity detect two retroviral oncogene products and inhibit their kinase activities - Sen, Stacy (1983)
Oligopeptides predicted from the nucleotide sequence of the oncogene v-fes of feline sarcoma virus (FeSV) were synthesized chemically and used to generate specific antibodies. Antisera against a 12-amino-acid-long oligopeptide (12-mer) located 42 residues from the carboxyl terminus of the v-fes coding sequence efficiently recognized the transforming proteins encoded by Snyder-Theilen (ST) and Gardner-Arnstein (GA) strains of FeSV. This 12-mer also contains 10 amino acid residues homologous in order and position to those predicted from the nucleotide sequence of the oncogene v-fps of avian Fujinami sarcoma virus (FSV). The anti-12-mer immunoprecipitated the FSV-specific transforming protein molecules from FSV-transformed cells. Binding of these antipeptide antibody molecules to the v-fes and the v-fps gene products inhibited their associated tyrosine-specific protein kinase (EC 2.7.1.37) activities. The ability to generate such site-specific antisera to the products of related oncogenes will be valuable in the molecular characterization of retroviral transforming proteins and their normal cellular homologs.